Preparation method of cube-like nano calcium carbonate

By controlling the calcination and carbonization reaction conditions of limestone and using composite additives to regulate the crystal form and morphology of nano calcium carbonate, the crystal form and morphology of nano calcium carbonate in the production of high-magnesium limestone is solved, avoiding product quality fluctuations, and realizing product Quality and performance stability.

CN119320156APending Publication Date: 2025-01-17GUANGXI ZHUANG AUTONOMOUS REGION INST OF METROLOGY & TESTING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411513356.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the industrial production of nano calcium carbonate, high-magnesium content limestone ore causes problems such as mixed crystal forms, irregular morphological doping, irregular particle size and poor uniformity, and commonly used additives such as sodium hydroxide and potassium hydroxide will cause problems such as The product's hygroscopicity enhancement and alkali reflux problems affect product quality and performance.

Method used

By calcining limestone with high magnesium content into calcium oxide and reacting with water to make a calcium hydroxide suspension, carburizing reaction and adding composite additives, such as soluble zinc salt and iminodiacetic acid, the carbonization reaction conditions and process parameters are controlled. , regulate the crystal form and morphology of nano calcium carbonate to avoid quality problems caused by additives.

Benefits of technology

It effectively solves the problems of mixed crystal forms, irregular morphology and poor uniformity in the preparation of nano calcium carbonate of high-magnesium limestone, avoids the problems of product hygroscopicity and alkali reflux, and ensures the stability of product quality and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320156A_ABST
    Figure CN119320156A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of cube-like nano calcium carbonate. The preparation method comprises the following steps: calcining raw material limestone with high magnesium content into calcium oxide with certain activity, digesting, refining, removing impurities and preparing into calcium hydroxide suspension; a composite additive accounting for 1%-5% of the solid content of calcium hydroxide in the suspension liquid is added when the carbonization reaction is carried out for 5 min, a cellulose-based surfactant accounting for 1%-2% of the theoretical yield of the nano calcium carbonate is added when the conductivity of the system starts to be obviously and continuously reduced, the reaction is carried out for 5 min when the conductivity of the system is reduced to an inflection point, the carbonization reaction is terminated, and the nano calcium carbonate suspension liquid is obtained; and carrying out filter pressing, drying, crushing and grading to obtain the cube-like nano calcium carbonate. By controlling the calcination degree of the limestone, controlling the process conditions of the carbonization reaction and using the synergistic effect of the composite additive, the crystal form and the morphology of the nano calcium carbonate are regulated and controlled, and the problems of product crystal form mixing, irregular morphology doping, irregular particle size, poor uniformity and the like which easily occur in the process of producing the nano calcium carbonate from the high-magnesium limestone are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of calcium carbonate preparation, in particular to a method for preparing cubic nano calcium carbonate. Background Art

[0002] Nano calcium carbonate is an excellent inorganic filler with a wide range of industrial applications. The application fields and application performance of nano calcium carbonate with different morphologies are slightly different. Quasi-cubic nano calcium carbonate has excellent performance, can be customized and has relatively stable product quality. It is mainly used in the rubber industry, plastic products, ink industry, sealant industry and coating industry. It is the product with the largest demand in the market. In industrial production, quasi-cubic nano calcium carbonate products are often affected by impurities in limestone ore raw materials, which affects product quality and product performance. The impact of magnesium impurities is particularly obvious. If the content of magnesium impurities in the limestone ore raw materials is too high, some rod-shaped, chain-shaped and other different crystal forms and morphologies of calcium carbonate will be mixed in, resulting in uneven product particle size and irregular morphology. What's more, it will generate micron-sized light calcium carbonate with larger particle size, which greatly destroys the uniformity of the product, affects the application performance of the product, and seriously lowers the product grade and market price. Sun Hongjuan, Chang Youjun (DOI: 10.3969 / j.issn.1004-4051.2005.02.024); Xu Wenxuan (DOI: CNKI: CDMD: 2.1016.227227); Sun Ling, He Liqiu, Wang Jilin, et al. (DOI: 10.3969 / j.issn.1001-9677.2022.17.015) found that a certain concentration of magnesium ions in the reaction system can induce the formation of aragonite-type rod-shaped calcium carbonate or aragonite-type calcium carbonate whiskers with a certain aspect ratio. Yu Yuxiang and Chen Xuemei (DOI: 10.3969 / j.issn.1006-4990.2015.12.011) found that as the magnesium content in lime milk increases, the average particle size of the generated nano-calcium carbonate particles gradually decreases, the specific surface area increases, and the number of chain-like particles increases. When the magnesium content of lime milk is greater than 1.17%, the particle size of calcium carbonate decreases significantly, the specific surface area increases rapidly, and the chain particles increase rapidly. Therefore, in the preparation process of nano calcium carbonate, the magnesium content in lime milk should be controlled below 1.17%. Ruan Siyu (DOI: 10.27461 / d.cnki.gzjdx.2023.000278) found that magnesium ions inhibit the formation of calcite-type calcium carbonate (cubic nano calcium carbonate belongs to calcite type); magnesium ions will cause significant changes in the morphology of calcium carbonate products by adsorbing on the crystal surface or inserting into the crystal lattice. When the magnesium ion content is low, CaCO3 is still a rhombohedron, and when Mg 2+ When the content rises to 5%, the product becomes small worm-like particles with rough surface, and the particles aggregate; high concentration of magnesium ion impurities will increase the particle size of calcium carbonate particles, which is not conducive to the formation of nano calcium carbonate.

[0003] Patent CN 109650430 A discloses a method for preparing nano calcium carbonate from limestone with high magnesium content, wherein sodium hydroxide and sodium polyacrylate are added during the carbonization reaction of preparing nano calcium carbonate from limestone with high magnesium content (magnesium content of 1.5%-4.4%) to increase the absorption rate of carbon dioxide in the system and promote the growth of calcium carbonate, while reducing the surface energy of the crystal plane where magnesium ions are dissolved, thereby reducing the agglomeration of calcium carbonate grains to form a chain structure, and adding disodium EDTA to the calcium carbonate slurry to modify the crystal surface, effectively solving the problem of the influence of magnesium impurities on the morphology of nano calcium carbonate, and preparing cubic nano calcium carbonate with uniform particle size and good dispersibility. However, the introduction of sodium in the production process can easily cause problems such as increased hygroscopicity and severe alkali return of nano calcium carbonate products that trouble many manufacturers, causing quality problems such as abnormal increase in moisture and pH value during product storage, affecting product quality and its application performance.

[0004] Patent CN 117069136 A discloses a method for preparing cubic nano-calcium carbonate from high-magnesium limestone by carbonization. The method controls the process parameters in the preparation of cubic nano-calcium carbonate, mainly uses a composite solution of ammonia water and sodium hydroxide or potassium hydroxide as a pH regulator for the refined lime slurry emulsion, and adjusts and maintains the pH of the refined lime slurry emulsion to be greater than 12.5 before the carbonization reaction and within the time period of 5min-15min of the carbonization reaction, thereby preparing small-particle-size nano-calcium carbonate seeds, and then directly adding an emulsifying dispersant to the reaction system, and simultaneously using a specially designed carbonization reactor for carbonization reaction, thereby solving the problem of chain-shaped and spindle-shaped calcium carbonate and poor crystal morphology when preparing cubic nano-calcium carbonate from high-magnesium limestone with a magnesium content of 5%-15%. However, the addition of strong alkaline additives such as sodium hydroxide and potassium hydroxide in the same production process still cannot avoid the problems of enhanced hygroscopicity and severe alkali return of nano-calcium carbonate products, and the abnormal increase of product moisture and pH value during storage, which affects the product quality and its application performance.

[0005] At present, in the industrial production process of nano calcium carbonate, it is usually ideal to adjust the magnesium content of the limestone raw material used according to the actual production conditions to be no more than 1% (measured by the magnesium carbonate content in the limestone). However, the quality of limestone ores in different mining areas is different, the distribution is complex, and the high-quality limestone ores are in short supply to nano calcium carbonate production enterprises, so it is inevitable to relax the quality of limestone entering the factory, and therefore it is difficult to strictly control or ensure the magnesium content of the ore used in the ideal situation during production. In order to solve the problems of crystal type mixing, irregular morphology doping, irregular particle size, poor uniformity, etc. that occur in the process of preparing nano calcium carbonate from high magnesium limestone, and to avoid the additives used to cause the nano calcium carbonate product to have strong hygroscopicity and alkali return, a preparation method of a cubic nano calcium carbonate is needed.

[0006] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed on the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0009] (1) The raw material limestone with high magnesium content is calcined at 900°C-1000°C to form calcium oxide, and the calcium oxide is digested and reacted with water at a temperature of 50°C-60°C, and then the calcium oxide is sieved through a 200-mesh screen to remove impurities and be refined to prepare a calcium hydroxide suspension of 1.035g / ml-1.065g / ml.

[0010] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is started for stirring, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 18° C.-27° C., a carbon dioxide mixed gas is introduced to start a carbonization reaction, and after reacting for 5 minutes, a composite additive of 1%-5% of the solid content of calcium hydroxide in the suspension is added, the mixture is stirred evenly, and the reaction is continued until the conductivity of the system begins to significantly and continuously decrease, and a cellulose-based surfactant of 1%-2% of the theoretical output of nano-calcium carbonate is added. When the conductivity of the system decreases to an inflection point, the reaction is continued for 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a nano-calcium carbonate suspension.

[0011] (3) At 70° C.-75° C., the nano-calcium carbonate suspension is surface treated with a hard fatty acid, and then filtered, dried, crushed, and classified to obtain cubic nano-calcium carbonate.

[0012] Preferably, the raw material limestone with a high magnesium content in step (1) has a magnesium content of 1.2% to 7% (calculated as the magnesium carbonate content in the raw material limestone).

[0013] Preferably, the activity of calcium oxide in step (1) is controlled to be a digestion rate t 60 ≤60s, t 60 It is the time required for the digestion temperature to reach 60℃ during the calcium oxide activity test.

[0014] Preferably, the carbon dioxide mixed gas in step (2) is a gas mixed with carbon dioxide and air or nitrogen, and the carbon dioxide gas concentration is 35%-50% during the reaction 0-5 minutes, and the carbon dioxide gas concentration is 30%-35% after 5 minutes until the reaction is terminated.

[0015] Preferably, in step (2), the carbon dioxide mixed gas is introduced into the reaction mixture for 0-5 min, and the concentration of the mixed gas is controlled to be higher than the concentration introduced for 5 min until the reaction is terminated.

[0016] Preferably, the stirring rate of the reactor in step (2) is controlled at 500 rpm-800 rpm during the reaction time 0-5 min, and is controlled at 300 rpm-500 rpm from 5 min to the termination of the reaction.

[0017] Preferably, in the first half of the carbonization reaction process in step (2), circulating cooling water is used to control the temperature of the reaction system below 30°C.

[0018] Preferably, the composite additive in step (2) is a composite of a soluble zinc salt and one or more of iminodiacetic acid, aminotriacetic acid, polyquaternium-6, and tetrabutyl titanate.

[0019] Preferably, the composite additive in step (2) comprises a soluble zinc salt and a main additive, the main additive comprises a composite of one or more of iminodiacetic acid, aminotriacetic acid, polyquaternium-6, and tetrabutyl titanate, and the added weight ratio of the soluble zinc salt to the main additive is 1:1.5-2.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0021] 1. The present invention adopts the carbonization method commonly used in industrial production. By controlling the degree of limestone calcination, controlling the process conditions of the carbonization reaction, and using the synergistic effect of composite additives, the crystal form and morphology of nano calcium carbonate are regulated, and the problems of product crystal mixture, irregular morphology, irregular particle size, and poor uniformity that are prone to occur in the process of producing nano calcium carbonate from high-magnesium content limestone are effectively solved.

[0022] 2. The additives used in the present invention will not affect the quality of cubic nano-calcium carbonate, and will not cause quality fluctuations and unstable quality problems such as abnormal increase in moisture content and severe alkali return during the storage period of the product.

[0023] 3. Currently, low-grade limestone ore is mostly used to produce low-priced primary product heavy calcium carbonate powder, or directly sold at a low price as building filler, etc. The present invention provides a new idea for the high-value and efficient utilization of high-magnesium limestone ore, which helps to alleviate the problem of insufficient supply of limestone ore raw materials for nano calcium carbonate enterprises. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope photograph of the nano-calcium carbonate in Example 1 of the present invention.

[0025] Figure 2 This is a scanning electron microscope photograph of nano-calcium carbonate in Example 2 of the present invention.

[0026] Figure 3 This is a scanning electron microscope photograph of the nano-calcium carbonate in Example 3 of the present invention.

[0027] Figure 4 This is a scanning electron microscope photograph of the nano-calcium carbonate in Comparative Example 1 of the present invention.

[0028] Figure 5 This is a scanning electron microscope photo of the nano calcium carbonate in Comparative Example 2 of the present invention.

[0029] Figure 6 This is a scanning electron microscope photograph of the nano-calcium carbonate in Comparative Example 3 of the present invention.

[0030] Figure 7 This is a scanning electron microscope photograph of the nano-calcium carbonate in Comparative Example 4 of the present invention.

[0031] Figure 8 This is a scanning electron microscope photograph of nano-calcium carbonate in Comparative Example 5 of the present invention.

[0032] Fig. 9 This is a scanning electron microscope photograph of nano-calcium carbonate in Comparative Example 6 of the present invention. DETAILED DESCRIPTION

[0033] The following embodiments may help those skilled in the art to more fully understand the present invention, but shall not limit the present invention in any way.

[0034] Example 1

[0035] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0036] (1) Raw limestone with a magnesium content of 1.2% (calculated as the magnesium carbonate content in the raw limestone) was calcined at 1000°C to obtain a digestion rate t 60 The calcium oxide with a reaction time of 58s is digested with water at a temperature of 50°C, and then the calcium oxide is sieved through a 200-mesh screen to remove impurities and is refined to prepare a 1.065g / ml calcium hydroxide suspension.

[0037] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is opened, the stirring rate is controlled to be 500 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 27° C., and the cooling circulating water is kept open in the first half of the reaction to control the temperature of the reaction system below 30° C. A carbon dioxide and air mixed gas with a carbon dioxide concentration of 35% is introduced to start the carbonization reaction. After reacting for 5 minutes, 0.4% zinc chloride and 0.6% aminotriacetic acid based on the solid content of calcium hydroxide in the suspension are added as composite additives, stirred evenly, and the carbon dioxide concentration is adjusted to 30%. The reaction is continued until the conductivity of the system begins to decrease significantly and continuously in the later stage, and 1% cellulose-based surfactant based on the theoretical output of nano calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for another 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a nano calcium carbonate suspension.

[0038] (3) At 70° C., the nano-calcium carbonate suspension is surface treated with hard fatty acid, and then filtered, dried, crushed, and classified to obtain cubic nano-calcium carbonate.

[0039] Example 2

[0040] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0041] (1) Raw limestone with a magnesium content of 5.2% (calculated based on the magnesium carbonate content in the raw limestone) was calcined at 950°C to obtain a digestion rate t 60 The calcium oxide with a reaction time of 49s is digested with water at a temperature of 60°C, and then the calcium oxide is sieved through a 200-mesh screen to remove impurities and is refined to prepare a 1.050g / ml calcium hydroxide suspension.

[0042] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is opened, the stirring rate is controlled to 600 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 23° C., and the cooling circulating water is kept open in the first half of the reaction to control the temperature of the reaction system below 30° C. A carbon dioxide and air mixed gas with a carbon dioxide concentration of 50% is introduced to start the carbonization reaction. After reacting for 5 minutes, 3% of zinc sulfate, iminodiacetic acid (IDA), and tetrabutyl titanate composite additives based on the solid content of calcium hydroxide in the suspension are added, the stirring rate is adjusted to 300 rpm, the mixture is stirred evenly, and the carbon dioxide concentration is adjusted to 35%. The reaction is continued until the conductivity of the system begins to decrease significantly and continuously in the later stage, and 1.5% of cellulose-based surfactant based on the theoretical yield of nano calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a nano calcium carbonate suspension.

[0043] (3) At 75° C., the nano-calcium carbonate suspension is surface treated with hard fatty acid, and then filtered, dried, crushed, and classified to obtain cubic nano-calcium carbonate.

[0044] Example 3

[0045] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0046] (1) Raw limestone with a magnesium content of 7.0% (calculated as the magnesium carbonate content in the raw limestone) was calcined at 900°C to obtain a digestion rate t 60 The calcium oxide with a reaction time of 41s is digested with water at a temperature of 60°C, and then the calcium oxide is sieved through a 200-mesh screen to remove impurities and be refined to prepare a 1.035g / ml calcium hydroxide suspension.

[0047] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is opened, the stirring rate is controlled to 800 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 18° C., and the cooling circulating water is kept open in the first half of the reaction to control the temperature of the reaction system below 30° C. A carbon dioxide and nitrogen mixed gas with a carbon dioxide concentration of 50% is introduced to start the carbonization reaction. When the reaction lasts for 5 minutes, 2% zinc chloride, 0.5% aminotriacetic acid, 0.5% polyquaternium salt-6, and 2% tetrabutyl titanate based on the solid content of calcium hydroxide in the suspension are added as composite additives, the stirring rate is adjusted to 400 rpm, the mixture is stirred evenly, and the carbon dioxide concentration is adjusted to 30%. The reaction is continued until the conductivity of the system begins to decrease significantly and continuously in the later stage, and 2% cellulose-based surfactant based on the theoretical yield of nano calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a nano calcium carbonate suspension.

[0048] (3) At 75° C., the nano-calcium carbonate suspension is surface treated with hard fatty acid, and then filtered, dried, crushed, and classified to obtain cubic nano-calcium carbonate.

[0049] Comparative Example 1

[0050] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0051] (1) Raw limestone with a magnesium content of 5.2% (calculated based on the magnesium carbonate content in the raw limestone) was calcined at 950°C to obtain a digestion rate t 60 The calcium oxide with a reaction time of 49s is digested with water at a temperature of 60°C, and then the calcium oxide is sieved through a 200-mesh screen to remove impurities and is refined to prepare a 1.050g / ml calcium hydroxide suspension.

[0052] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is opened, the stirring rate is controlled to 300 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 27° C., a mixture of carbon dioxide and air with a carbon dioxide concentration of 15% is introduced to start a carbonization reaction, and after reacting for 5 minutes, the stirring rate is adjusted to 600 rpm, the carbon dioxide concentration is adjusted to 50%, and the reaction is continued until the conductivity of the system begins to significantly and continuously decrease in the later stage, and 1.5% cellulose-based surfactant based on the theoretical output of nano-calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for another 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a calcium carbonate product suspension.

[0053] (3) At 75° C., the calcium carbonate product suspension is surface treated with a hard fatty acid, and then filtered, dried, crushed, and classified to obtain the calcium carbonate product.

[0054] Comparative Example 2

[0055] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0056] (1) Raw limestone with a magnesium content of 5.2% (calculated based on the magnesium carbonate content in the raw limestone) was calcined at 1050°C to obtain a digestion rate t 60 The calcium oxide with a temperature of 121s is digested and reacted with water at a temperature of 60°C, and then sieved through a 200-mesh screen to remove impurities and purify it, and then prepared into a 1.050g / ml calcium hydroxide suspension.

[0057] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is turned on, the stirring rate is controlled to 600 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 23° C., and the cooling circulating water is kept on in the first half of the reaction to control the temperature of the reaction system below 30° C. A carbon dioxide and air mixture with a carbon dioxide concentration of 50% is introduced to start the carbonization reaction. After reacting for 5 minutes, the stirring rate is adjusted to 300 rpm, and the carbon dioxide concentration is adjusted to 35%. The reaction is continued until the conductivity of the system begins to decrease significantly and continuously in the later stage, and a 1.5% cellulose-based surfactant based on the theoretical yield of nano-calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for another 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a calcium carbonate product suspension.

[0058] (3) At 75° C., the calcium carbonate product suspension is surface treated with a hard fatty acid, and then filtered, dried, crushed, and classified to obtain the calcium carbonate product.

[0059] Comparative Example 3

[0060] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0061] (1) Raw limestone with a magnesium content of 5.2% (calculated based on the magnesium carbonate content in the raw limestone) was calcined at 1050°C to obtain a digestion rate t 60 The calcium oxide with a temperature of 121s is digested and reacted with water at a temperature of 60°C, and then sieved through a 200-mesh screen to remove impurities and purify it, and then prepared into a 1.050g / ml calcium hydroxide suspension.

[0062] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is opened, the stirring rate is controlled to 300 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 27° C., a carbon dioxide and air mixture with a carbon dioxide concentration of 15% is introduced to start a carbonization reaction, and after reacting for 5 minutes, 1% zinc sulfate, 1% iminodiacetic acid (IDA), and 1% tetrabutyl titanate are added as composite additives based on the solid content of calcium hydroxide in the suspension, the stirring rate is adjusted to 600 rpm, the mixture is stirred evenly, and the carbon dioxide concentration is adjusted to 50%, and the reaction is continued until the conductivity of the system begins to decrease significantly and continuously in the later stage, and 1.5% cellulose-based surfactant based on the theoretical output of nano-calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a calcium carbonate product suspension.

[0063] (3) At 75° C., the calcium carbonate product suspension is surface treated with a hard fatty acid, and then filtered, dried, crushed, and classified to obtain the calcium carbonate product.

[0064] Comparative Example 4

[0065] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0066] (1) Raw limestone with a magnesium content of 5.2% (calculated based on the magnesium carbonate content in the raw limestone) was calcined at 950°C to obtain a digestion rate t 60 The calcium oxide with a reaction time of 49s is digested with water at a temperature of 60°C, and then the calcium oxide is sieved through a 200-mesh screen to remove impurities and is refined to prepare a 1.050g / ml calcium hydroxide suspension.

[0067] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is turned on, the stirring rate is controlled to 600 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 23° C., and the cooling circulating water is kept on in the first half of the reaction to control the temperature of the reaction system below 30° C. A carbon dioxide and air mixture with a carbon dioxide concentration of 50% is introduced to start the carbonization reaction. After reacting for 5 minutes, the stirring rate is adjusted to 300 rpm, and the carbon dioxide concentration is adjusted to 35%. The reaction is continued until the conductivity of the system begins to decrease significantly and continuously in the later stage, and a 1.5% cellulose-based surfactant based on the theoretical yield of nano-calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for another 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a calcium carbonate product suspension.

[0068] (3) At 75° C., the calcium carbonate product suspension is surface treated with a hard fatty acid, and then filtered, dried, crushed, and classified to obtain the calcium carbonate product.

[0069] Comparative Example 5

[0070] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0071] (1) Raw limestone with a magnesium content of 5.2% (calculated based on the magnesium carbonate content in the raw limestone) was calcined at 950°C to obtain a digestion rate t 60 The calcium oxide with a reaction time of 49s is digested with water at a temperature of 60°C, and then the calcium oxide is sieved through a 200-mesh screen to remove impurities and is refined to prepare a 1.050g / ml calcium hydroxide suspension.

[0072] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is opened, the stirring rate is controlled to 300 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 27° C., a carbon dioxide and air mixture with a carbon dioxide concentration of 15% is introduced to start a carbonization reaction, and after reacting for 5 minutes, 1% zinc sulfate, 1% iminodiacetic acid, and 1% tetrabutyl titanate are added as composite additives based on the solid content of calcium hydroxide in the suspension, the stirring rate is adjusted to 600 rpm, the mixture is stirred evenly, and the carbon dioxide concentration is adjusted to 50%, and the reaction is continued until the conductivity of the system begins to significantly and continuously decrease in the later stage, and 1.5% cellulose-based surfactant based on the theoretical output of nano calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a calcium carbonate product suspension.

[0073] (3) At 75° C., the calcium carbonate product suspension is surface treated with a hard fatty acid, and then filtered, dried, crushed, and classified to obtain the calcium carbonate product.

[0074] Comparative Example 6

[0075] A method for preparing cubic nano calcium carbonate comprises the following steps:

[0076] (1) Raw limestone with a magnesium content of 5.2% (calculated based on the magnesium carbonate content in the raw limestone) was calcined at 1050°C to obtain a digestion rate t 60 The calcium oxide with a temperature of 121s is digested and reacted with water at a temperature of 60°C, and then sieved through a 200-mesh screen to remove impurities and purify it, and then prepared into a 1.050g / ml calcium hydroxide suspension.

[0077] (2) The calcium hydroxide suspension is fed into a jacketed reactor, the reactor is opened, the stirring rate is controlled to 600 rpm, cooling circulating water is introduced to adjust the temperature of the calcium hydroxide suspension to 23° C., and the cooling circulating water is kept open in the first half of the reaction to control the temperature of the reaction system below 30° C. A carbon dioxide and air mixed gas with a carbon dioxide concentration of 50% is introduced to start the carbonization reaction. After reacting for 5 minutes, 1% zinc sulfate, 1% iminodiacetic acid, and 1% tetrabutyl titanate based on the solid content of calcium hydroxide in the suspension are added as composite additives, the stirring rate is adjusted to 300 rpm, the mixture is stirred evenly, and the carbon dioxide concentration is adjusted to 35%. The reaction is continued until the conductivity of the system begins to decrease significantly and continuously in the later stage, and 1.5% cellulose-based surfactant based on the theoretical output of nano calcium carbonate is added. When the conductivity of the system drops to the inflection point, the reaction is continued for 5 minutes, and the ventilation is stopped to terminate the carbonization reaction to obtain a calcium carbonate product suspension.

[0078] (3) At 75° C., the calcium carbonate product suspension is surface treated with a hard fatty acid, and then filtered, dried, crushed, and classified to obtain the calcium carbonate product.

[0079] The finished nano calcium carbonate prepared in the embodiment of the present invention and the comparative example was tested according to the GB / T 19281-2014 calcium carbonate analysis method, and the crystal form was characterized by X-ray diffraction (XRD), and the results were as follows:

[0080]

[0081] As can be seen from the test and characterization results in the above table, the nano calcium carbonate crystal form prepared by Examples 1-3 of the present invention is calcite-type, with a single, relatively regular cubic shape, a relatively uniform particle size, and an average particle size of less than 100nm. At the same time, the moisture and pH value change normally during the storage of the product. The moisture content of the product is less than 0.65% and the pH value is less than 10 after 60 days of storage, which are all kept within a reasonable level and do not affect the product quality and product performance. Compared with Example 2, Comparative Examples 1-3 control the limestone calcination degree, carbonization reaction process conditions and composite additives separately, and Comparative Examples 4-6 control two of the limestone calcination degree, carbonization reaction process conditions and composite additives simultaneously. From the characterization results of X-ray diffraction (XRD) and scanning electron microscopy, it can be seen that the calcium carbonate crystal form obtained in Comparative Example 1 is a doping of calcite and aragonite, and the morphology is a mixture of chain-like and quasi-cubic shapes, the calcium carbonate crystal form obtained in Comparative Example 2 is a calcite type, and the morphology is a mixture of spindle-like and rod-like shapes, the calcium carbonate crystal form obtained in Comparative Example 3 is a doping of calcite and aragonite, and the morphology is a mixture of rod-like and quasi-cubic shapes, the calcium carbonate crystal form obtained in Comparative Example 4 is a calcite type, and the morphology is a mixture of long-chain locks and quasi-cubic shapes, the calcium carbonate crystal form obtained in Comparative Example 5 is a doping of calcite and aragonite, and the morphology is a mixture of rod-like and quasi-cubic shapes, and the calcium carbonate crystal form obtained in Comparative Example 6 is a doping of calcite and aragonite, and the morphology is a mixture of rod-like, quasi-cubic and spindle-like shapes. None of them can obtain nano calcium carbonate with a single crystal form and a relatively regular cubic morphology. It can be seen from this that it is necessary to control the degree of calcination of limestone, control the process conditions of the carbonization reaction, use the synergistic effect of composite additives, and regulate the crystal form and morphology of nano-calcium carbonate in order to obtain nano-calcium carbonate with a single crystal form and a relatively regular cubic morphology, and solve the problems of product crystal mixture, irregular morphology, irregular particle size, and poor uniformity in the process of producing nano-calcium carbonate from high-magnesium content limestone.

[0082] The above generally describes the present invention in detail, but it is obvious to a person skilled in the art that some modifications or improvements can be made to the present invention. Therefore, modifications or improvements that do not depart from the spirit of the present invention are within the scope of protection of the present invention.

Claims

1. A method for preparing cubic nano calcium carbonate, characterized in that: The following steps are involved: (1) calcining raw material limestone with high magnesium content at 900° C.-1000° C. into calcium oxide, digesting the calcium oxide with water at a temperature of 50° C.-60° C., sieving through a 200-mesh screen to remove impurities and purify the mixture, and preparing a calcium hydroxide suspension of 1.035 g / ml-1.065 g / ml; (2) feeding the calcium hydroxide suspension into a jacketed reactor, starting the reactor to stir, introducing cooling circulating water to adjust the temperature of the calcium hydroxide suspension to 18° C.-27° C., introducing a carbon dioxide mixed gas to start a carbonization reaction, and reacting for 5 minutes, adding a composite additive of 1%-5% of the solid content of calcium hydroxide in the suspension, stirring evenly, and continuing the reaction until the conductivity of the system begins to significantly and continuously decrease, adding a cellulose-based surfactant of 1%-2% of the theoretical output of nano-calcium carbonate, and reacting for another 5 minutes when the conductivity of the system drops to an inflection point, stopping the ventilation to terminate the carbonization reaction, and obtaining a nano-calcium carbonate suspension; (3) At 70° C.-75° C., the nano-calcium carbonate suspension is surface treated with a hard fatty acid, and then filtered, dried, crushed, and classified to obtain cubic nano-calcium carbonate.

2. The method for preparing cubic nano calcium carbonate according to claim 1, wherein: The raw material limestone with high magnesium content in step (1) has a magnesium content of 1.2%-7%, where the magnesium content is calculated based on the magnesium carbonate content in the raw material limestone.

3. The preparation method of cubic nano calcium carbonate according to claim 1, wherein: The activity of calcium oxide in step (1) is controlled by the digestion rate t 60 ≤60s.

4. The method for preparing cubic nano calcium carbonate according to claim 1, wherein: The carbon dioxide mixed gas in step (2) is a gas mixed with carbon dioxide and air or nitrogen. The carbon dioxide gas concentration is 35%-50% during the reaction time of 0-5 minutes, and the carbon dioxide gas concentration is 30%-35% after 5 minutes until the reaction is terminated.

5. The method for preparing cubic nano calcium carbonate according to claim 1, wherein: Step (2) carbon dioxide mixed gas, control the concentration of the mixed gas introduced during the reaction from 0 to 5 minutes to be higher than the concentration introduced during the reaction until the reaction is terminated.

6. The method for preparing cubic nano calcium carbonate according to claim 1, wherein: The stirring rate of the reactor in step (2) is controlled at 500 rpm-800 rpm during the reaction time 0-5 min, and is controlled at 300 rpm-500 rpm from 5 min to the termination of the reaction.

7. The method for preparing cubic nano calcium carbonate according to claim 1, wherein: In the first half of the carbonization reaction process in step (2), circulating cooling water is used to control the temperature of the reaction system below 30°C.

8. The method for preparing cubic nano calcium carbonate according to claim 1, wherein: The composite additive in step (2) is a composite of a soluble zinc salt and one or more of iminodiacetic acid, aminotriacetic acid, polyquaternium-6, and tetrabutyl titanate.

9. The method for preparing cubic nano calcium carbonate according to claim 1, wherein: The composite additive in step (2) includes a soluble zinc salt and a main additive, the main additive includes one or more of iminodiacetic acid, aminotriacetic acid, polyquaternium-6, and tetrabutyl titanate, and the added weight ratio of the soluble zinc salt to the main additive is 1:1.5-2.

Citation Information

Patent Citations

  • Method for preparing nano-calcium carbonate from limestone with high magnesium content

    CN109650430A